The night bus - Bickers, Tessa (Mira, 2026)
One book. Two strangers. An unforgettable journey as they rewrite the ending. Daisy Douglas has spent her life behind the scenes: at work, in her relationships, and now, in planning a wedding she isn't sure she even wants. As an entertainment journalist, she can spot the start of a story a mile away. So when her routine 4 a.m. bus ride to the newsroom takes a surprising turn, she notices. For months, the same man has boarded at the same stop, reading the same tattered copy of Virginia Woolf's Orlando over and over as if his life depends on it. When a broken-down bus and a shared walk through the quiet early-morning London streets finally throws them together, Tom reveals the heartbreaking truth as to why he can't be without his novel. Determined to help him find the answer to the riddle hidden in its pages, Daisy joins Tom on his strange literary quest--one that leads them to places neither of them ever expected. But as their friendship deepens, she starts to wonder if what they're both looking for might not be in the book after all.